Testing MANET Protocol using Zigbee based Xbee Modules - S. Sundar; Piyush Arora; Sarthak Agrawal; R. Kumar; Harish M. Kittur (Institute of Advanced Engineering and Science, 2016)
In the last few years,there has been big interest in adhoc wireless network as they have tremendous military and commercial potential[1].Traditionally to test various parameters in the MANET , the most popular approach is to use mobile phone and Laptops and use the popular WIFI based protocol . But in the recent years there is a huge attraction towards the Internet Of things and specifically wireless sensor network. In this paper we are going to test the MANET protocol using zigbee based XBee modules specifally to determine the Range and Throughput of the Xbee netowork using XCTU Software . The sensor network will be deployed in the car parking application to see the parameters in the real time and dynamically see the sustainability of the network .The network is being designed keeping in mind that the nodes are mobile and at the same time the network does not require a standard infrastructure.